MicroRNA-223 ameliorates alcoholic liver injury by inhibiting the IL-6–p47phox–oxidative stress pathway in neutrophils. Issue 4 (27th September 2016) - Li, Man; He, Yong; Zhou, Zhou; Ramirez, Teresa; Gao, Yueqiu; Gao, Yanhang; Ross, Ruth A; Cao, Haixia; Cai, Yan; Xu, Mingjiang; Feng, Dechun; Zhang, Ping; et al.
Abstract : Objectives: Chronic-plus-binge ethanol feeding activates neutrophils and exacerbates liver injury in mice. This study investigates how recent excessive drinking affects peripheral neutrophils and liver injury in alcoholics, and how miR-223, one of the most abundant microRNAs (miRNAs) in neutrophils, modulates neutrophil function and liver injury in ethanol-fed mice. Designs: Three hundred alcoholics with (n=140) or without (n=160) recent excessive drinking and 45 healthy controls were enrolled. Mice were fed an ethanol diet for 10 days followed by a single binge of ethanol. Results: Compared with healthy controls or alcoholics without recent drinking, alcoholics with recent excessive drinking had higher levels of circulating neutrophils, which correlated with serum levels of alanine transaminase (ALT) and aspartate transaminase (AST). miRNA array analysis revealed that alcoholics had elevated serum miR-223 levels compared with healthy controls. In chronic-plus-binge ethanol feeding mouse model, the levels of miR-223 were increased in both serum and neutrophils. Genetic deletion of the miR-223 gene exacerbated ethanol-induced hepatic injury, neutrophil infiltration, reactive oxygen species (ROS) and upregulated hepatic expression of interleukin (IL)-6 and phagocytic oxidase (phox) p47 phox . Mechanistic studies revealed that miR-223 directly inhibited IL-6 expression and subsequently inhibited p47 phox expression in neutrophils. Deletion of the p47 phox gene ameliorated ethanol-induced liver injury and ROS production by neutrophils. Finally, miR-223 expression was downregulated, while IL-6 and p47 phox expression were upregulated in peripheral blood neutrophils from alcoholics compared with healthy controls. Conclusions: miR-223 is an important regulator to block neutrophil infiltration in alcoholic liver disease and could be a novel therapeutic target for the treatment of this malady.